2019
DOI: 10.1111/mmi.14407
|View full text |Cite|
|
Sign up to set email alerts
|

The UDP‐GalNAcA biosynthesis genes gnagne2 are required to maintain cell envelope integrity and in vivo fitness in multi‐drug resistant Acinetobacter baumannii

Abstract: Acinetobacter baumannii infects a wide range of anatomic sites including the respiratory tract and bloodstream. Despite its clinical importance, littleis known about the molecular basis of A. baumannii pathogenesis. We previously identified the UDP-N-acetyl-d-galactosaminuronic acid (UDP-GalNAcA) biosynthesis genes, gna-gne2, as being critical for survival in vivo. Herein, we demonstrate that Gna-Gne2 are part of a complex network connecting in vivo fitness, cell envelope homeostasis and resistance to antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
(234 reference statements)
0
4
0
Order By: Relevance
“…The UDP-GlcNAcA substrate is predicted to be generated via dehydrogenase activity at the C-6 position of UDP-GlcNAc by Gna, a homolog of WbpA in Pseudomonas aeruginosa and TviB in Salmonella enterica serovar Typhi ( 25 , 38 , 39 ). Previous reports have shown that the deletion of gna along with a downstream UDP-GlcNAcA C-4 epimerase gene, gne2 , results in partial truncation of the core oligosaccharide ( 40 ). Importantly, this GlcNAc precursor is an essential component of the peptidoglycan cell wall ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…The UDP-GlcNAcA substrate is predicted to be generated via dehydrogenase activity at the C-6 position of UDP-GlcNAc by Gna, a homolog of WbpA in Pseudomonas aeruginosa and TviB in Salmonella enterica serovar Typhi ( 25 , 38 , 39 ). Previous reports have shown that the deletion of gna along with a downstream UDP-GlcNAcA C-4 epimerase gene, gne2 , results in partial truncation of the core oligosaccharide ( 40 ). Importantly, this GlcNAc precursor is an essential component of the peptidoglycan cell wall ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…We suspect that lptE mutations only partially impair LOS transport, as has been observed in other bacteria ( 45 , 46 ). Other top meropenem sensitive mutants (classes 1 and 2 in Table S2 ) inactivated the genes for β-lactamase OXA-23, LOS modification enzymes ( lpxL and lpsB ), capsule synthesis genes ( wzy , wzb , and wzc ), a capsule biosynthetic enzyme also involved in LOS synthesis ( gna ) ( 47 ), and genes needed for disulfide bond formation ( dsbAB ), zinc transport ( znuABC and zurA ), regulation ( rpoE and rseP ), or peptidoglycan metabolism ( pbpG and ampG ). For the three β-lactamases other than OXA-23, only mutations inactivating GES-14 increased meropenem sensitivity, although the phenotype was relatively weak (class 4).…”
Section: Resultsmentioning
confidence: 99%
“…The capsule of A. baumannii has been shown to play significant roles in protection against several host processes. The capsule aids in resistance to desiccation, disinfectants, antimicrobials, and antibiotics, consequently mutations in genes responsible for capsule production severely affect virulence in vivo [ 15 , 16 , 17 , 18 , 19 ]. Similarly, alteration in capsule structure can impact virulence [ 20 ].…”
Section: Introductionmentioning
confidence: 99%